Resolution of Retinal Bleeding And Exudative Retinal Detachment After Chemotherapy with Melphalan In Multiple Myeloma - Ari Andayani; I Putu Budhiastra; I Wayan Losen Adnyana; Made Paramita Wijayati (International Journal of Retina, 2018)
Introduction: Multiple myeloma is the second most common hematologic cancer. It is characterized by the clonal proliferation of malignant plasma cells and associated organ dysfunction. Ophthalmic manifestations include hyperviscosity retinopathy and retinal detachment. The aim of this study is to report retinal manifestation in Multiple Myeloma. Methods: A man 45 years old, complained loss of vision on both eyes especially left eye over 1 month. He also feels weakness and 3 times spontaneous nose bleeding. His visual acquity is 6/12 on the right and 2/60 left eye with Retinal Bleeding and Retinal Detachment. His Laboratory examination result increase in WBC 65.91 x 103/µL (Neutrophil, Monocyte, Basophil and Lymphocyte) decrease RBC 3 x 106/µL, HGB 6.85 g/dL, normal PLT 193.60 103/µL, Normal Bleeding and Clotting Time and increase ESR 140 mm/hour. Multiple myeloma was diagnosed by Internal Department with bone marrow biopsy and increase of Gamma Globulin. Results: The patient was treated with melphalan 3 tablet 2 times a day and prednisone 4 mg 3 times a day for 5 days every 28 days. After 8 month the VA 6/6 on the right and 6/10 on the left with complete resolution of on the right eye and there are resolution on the left eye with fibrosis, the laboratory examination normal WBC 3.8 x 103/µL with Neutrophil 59.3%, Monocyte 6.1 %, Eosinophil 6.3 %, Basophil 0.3 % and Lymphocyte 28.0 %, normal RBC 4.6 x 106/µL, slightly decrease HGB 12.8 g/dL, normal PLT 177.0 x 103/µL and decrease Gamma Globulin. Discussion: This case of bilateral Retinal Bleeding and Exudative Retinal Detachment are remarkable for both its presentation and response to melphalan therapy. Treatment with melphalan and prednison alone was sufﬁcient to clear the Retinal Bleeding and restoration of Exudative Retinal Detachment. Conclusion: Complication of Multiple Myeloma can caused organ disfunction such as retinal bleeding and exudative retinal detachment. Early Diagnosis is very crucial. In our case combination cemotheraphy with Melphalan and Prednison showed clinically significant resolution. Workship Internal Department and Ophthalmology Department are very important for management and monitoring ophthalmology manifestation in multiple myeloma.